Sex in the digital city: location-based dating apps and queer urban life. Issue 11 (2nd November 2017) - Miles, Sam
Abstract: It is well established that digital technology and code mediate bodies in space. The collapse of any supposed physical/digital divide has been amply documented to the extent that everyday life is now widely theorised in terms of hybridisation. What is less clear is what comes next for those participating in this hybridisation. This article examines what Kitchin and Dodge term the 'social contour of software' via queer male locative media users who collectively negotiate digital hybridisation in their everyday lives. Using qualitative interviews with 36 non-heterosexual men using apps such as Grindr and Tinder in London, UK, I explore how locative media refigures conceptualisations of community, technological efficiency and boundaries between private and public space. The study finds that users express ambivalence about their membership of queer 'communities', and are also unconvinced by online sociality. Apps expedite searches for new partners but prove deceptively time-consuming. Public and private space are being hybridised by locative technology, but common codes of conduct are slower to develop, leaving users unsure of how to navigate physical encounter. This article concludes that schema for queer men's lives are increasingly promulgated digitally but may be uneasily embodied in everyday practice.